A 3D quantitative imaging biomarker in pre-treatment MRI predicts overall survival after stereotactic radiation therapy of patients with a singular brain metastasis. (November 2019) - Della Seta, Marta; Collettini, Federico; Chapiro, Julius; Angelidis, Alexander; Engeling, Fidelis; Hamm, Bernd; Kaul, David
Background: Brain metastases (BM) are the most frequent intracranial malignant tumor. Various prognostic factors facilitate the prediction of survival; however, few have become tools for clinical use. Purpose: To investigate the role of three-dimensional (3D) quantitative tissue enhancement in pre-treatment cranial magnetic resonance imaging (MRI) as a radiomic biomarker for survival (OS) in patients with singular BM treated with stereotactic radiation therapy (SRT). Material and Methods: In this retrospective study, 48 patients (27 non-small cell lung cancer and 21 melanoma) with singular BM treated with SRT, were analyzed. Contrast-enhanced MRI scans of the neurocranium were used for quantitative image analyses. Segmentation-based 3D quantification was performed to measure the enhancing tumor volume. A cut-off value of 68.61% of enhancing volume was used to stratify the cohort into two groups (≤68.61% and > 68.61%). Univariable and multivariable cox regressions were used to analyze the prognostic factors of OS and intracranial progression-free survival (iPFS). Results: The level of enhancing tumor volume achieved statistical significance in univariable and multivariable analysis for OS (univariable: P = 0.005, hazard ratio [HR] = 0.375, 95% confidence interval [CI] = 0.168–0.744; multivariable: P = 0.006, HR = 0.376, 95% CI = 0.186–0.757). Patients with high-level enhancement (>68.61% enhancing lesion volume) survived significantly longer (4.9 vs. 10.2 months) and showed significantly longer iPFS rates (univariable: P < 0.001, HR = 0.046, 95% CI = 0.009–0.245). Conclusions: Patients with lesions that show a higher percentage of enhancement in pre-treatment MRI demonstrated improved iPFS and OS compared to those with mainly hypo-enhancing lesions. Lesion enhancement may be a radiomic marker, useful in prognostic indices for survival prediction, in patients with singular BM.